ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENTABILITAS PADA BANK PERKREDITAN RAKYAT DI KOTA BATAM - Krisnawati, Kelly; JanrosL, Viola Syukrina (SCIENTIA JOURNAL, 2022)
The aim of this research is to find out the impact of loan to deposit ratio, third-party funds, and company size on rentability with the return on assets as a indicator at the rural banks in Batam City, either on partially or simultaneously. The research uses descriptive-quantitative type, with data periods ranging from 2017 to 2021. The population in this research consists of conventional rural banks located in Batam City with a total 28 banks then selected as samples using a purposive sampling method with several criteria applied. The data analysis technique used in this research is multiple linear regression analysis. Data analysis was performed using IBM SPSS 26 software. Study results shows that partially, loan to deposit ratio has a positive and significant effect on return on assets, third-party funds partially have a positive and significant effect on return on assets, while company size has a negative and insignificant effect on return on assets. Lastly, loan to deposit ratio, third-party funds, and company size have a significant effect on return on assets.